Elements of justice - Schmidtz, David (Cambridge University Press, 2006)
What is justice? Questions of justice are questions about what people are due. However, what that means in practice depends on the context in which the question is raised. Depending on context, the formal question of what people are due is answered by principles of desert, reciprocity, equality, or need. Justice, therefore, is a constellation of elements that exhibit a degree of integration and unity. Nonetheless, the integrity of justice is limited, in a way that is akin to the integrity of a neighborhood rather than that of a building. A theory of justice offers individuals a map of that neighborhood, within which they can explore just what elements amount to justice.